Perjanjian Kerjasama Antara Pt. Pertamina (Persero) dengan Pengusaha Agen Penyaluran dan Pemasaran Gas Elpiji 3 Kg - Rofi Kurniawan Rustandi; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2022)
The agreement is the thing that is most often done by everyone, thus, the act by one or more people binding himself to another person or more is the meaning of the agreement. The purpose of this study is to discuss the arrangement of the cooperation agreement between PT. Pertamina (Persero) with business agents for distribution and marketing of 3 Kg LPG and to examine the process of realizing the balance of rights and obligations in the cooperation agreement between PT. Pertamina (Persero) with business agents for distribution and marketing of 3 Kg LPG gas. This study uses a normative legal research method, with a statutory approach and a conceptual approach. The primary sources of legal material for this research are the Civil Code, Law No. 19 of 2003 and Law No. 22 of 2001. The secondary sources of legal materials for this research are law books or legal journals. Data collection techniques using recording techniques, file systems, and document studies which will be analyzed systematically. The results obtained from this study are the legal basis for the arrangement of the agreement in the Civil Code Articles 1313, 1320, and 1338, as well as the arrangement of the balance of rights and obligations of the cooperation agreement as regulated in the Agency Law. The government pays attention to the business activity sector by business actors, regarding the clauses of the 3 Kg LPG agency agreement